Evaluation of Larvicidal Activity of Ageratina adinophora Spreng King H Rob against Culex quinquefasciatus Say - Dhanasekaran, S (International Journal of Pharmaceutical & Biological Archive, 2014)
Evaluation of Larvicidal Activity of Ageratina adinophora Spreng King H Rob against Culex quinquefasciatus Say